Embracing Uncertainty: John Keats’s Negative Capability and its Romantic Legacy - Adhikary, Ramesh Prasad (Academia Research Journal, 2024)
This research paper delves into John Keats's concept of Negative Capability, a pivotal idea in the Romantic literary tradition, which emphasizes the poet's ability to remain in uncertainties and mysteries without the irritable reaching after fact and reason. Originating from Keats’s letter to his brothers in 1817, this concept challenges the Enlightenment’s rationalist approach, advocating for a more intuitive and imaginative understanding of human experience. The primary objective of this study is to comprehensively analyze Keats’s articulation of Negative Capability, its manifestation in his poetry, and its broader implications within the Romantic tradition and subsequent literary movements. This study enhances the understanding of Romantic literature, offers insights into Keats's poetic philosophy, and highlights the enduring influence of Negative Capability on modern literary theory and creative practices. The research employs a qualitative methodology grounded in close reading, historical analysis, and comparative analysis. Primary texts include Keats’s letters and major poems, while secondary sources encompass critical essays and scholarly works on Keats and Romanticism. The analysis reveals that Negative Capability is central to Keats’s major works, such as "Ode on a Grecian Urn," "Ode to a Nightingale," and "To Autumn." These poems exemplify Keats's embrace of ambiguity, beauty, and transience, reflecting his resistance to rational explanations and his celebration of the unknown and the mysterious. The study also identifies the concept’s influence on later literary movements, particularly Modernism and Postmodernism, which similarly grapple with themes of uncertainty and existential doubt. John Keats’s Negative Capability represents a profound acceptance of life’s uncertainties and the mysteries of artistic creation. This study underscores its significance in Keats's work and its lasting impact on the literary landscape, reaffirming the importance of embracing ambiguity and the transformative power of art.